Latvia : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 1998)
This Selected Issues paper and Statistical Appendix highlights that the real GDP growth in Latvia accelerated in the second half of 1997, and is estimated at 6 percent for the year. Growth was broad-based, with particularly strong performance in the services sector and construction, and has been led by increased investment, with real capital formation rising by an estimated 10 percent, and enhanced efficiency. Reflecting the strong economic growth, official unemployment has begun to decline, falling from 7 1\2 percent in mid-year to 6.7 percent at end-January 1998.